Potret Perubahan Kelekatan Emosi Ibu dan Anak di Masa Belajar Online dari Rumah: Portraits of Changes in The Emotional Attachment of Mother and Child on Learning Online from Home - Eny Suprihatin; Ruthias Yusuarsi (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Learning from home is a policy taken by the government to prevent the spread of COVID-19 and protect the public. This study uses a qualitative phenomenological method. To reveal the phenomena in connection with the implementation of learning from home to changes in the emotional attachment of mothers and children during the learning period from home during the COVID-19 pandemic. The respondents were six mothers and their children. The study results show that there is indeed an estrangement between mother and child in terms of emotional attachment, namely two mothers with each child. However, the mother is a strong effort as the primary attachment figure to repair the relationship and warmth so that the estrangement for two children can be attached.